Pattern of Haematological Abnormalities in Malnourished Children Presenting to a Tertiary Care Hospital - Muhammad, Mian; Mohammad, Amir; Rahman, Momina; Sami Ullah,; Shafiq, Fatima; Syed, Annam (Indus Journal of Bioscience Research, 2025)
Background: Severe Acute Malnutrition (SAM) is a major public health concern and a leading contributor to childhood morbidity and mortality, particularly in low- and middle-income countries like Pakistan. Haematological abnormalities, including anemia, leukocytosis, thrombocytopenia, and pancytopenia, are frequently observed in malnourished children, often compounding clinical outcomes. Objective: To evaluate the pattern of haematological abnormalities in children aged 1–5 years with SAM presenting to a tertiary care hospital. Methods: A descriptive cross-sectional study was conducted at Lady Reading Hospital, Peshawar, from November 2, 2023, and May 2, 2024. A total of 177 children diagnosed with SAM were enrolled using consecutive non-probability sampling. Demographic data and blood samples were collected. Hematological parameters including hemoglobin levels, white blood cells, and platelets were analyzed. Data were stratified by age, gender, maternal education, and socioeconomic status. Results: Anemia was the most prevalent abnormality, affecting 84.2% of participants, with moderate anemia being the most common subtype (36.7%). Thrombocytopenia (26.6%), leukocytosis (22.0%), and pancytopenia (20.3%) were also significantly observed. Stratification analysis revealed a statistically significant association of anemia with younger age (p = 0.042), low maternal education (p = 0.031), and low socioeconomic status. Thrombocytopenia was significantly more prevalent among children from poorer households (p = 0.026). Conclusion: A high burden of hematological abnormalities was identified among SAM children, with anemia being most prominent. These findings emphasize the need for routine haematological assessment in the management of malnourished children to enable early intervention and improved clinical outcomes.